(untitled) (Research, Society and Development, 2026)
The use of injectable materials for male penile augmentation has increased considerably over the past decade, yet the supporting scientific evidence remains limited and fragmented. The objective of this article is to identify, analyze, and synthesize the available scientific evidence on the safety profile and associated risks of the different materials used for male penile filling, with the aim of providing a sounder foundation for safer clinical practice and advancing the ethical and scientific debate surrounding this emerging aesthetic procedure. An integrative review was performed following the six-step framework proposed by Mendes, Silveira, and Galvão, with searches conducted in PubMed/MEDLINE, Web of Science, SciELO, and LILACS/BVS between March and April 2025. Seventeen studies met the full eligibility criteria and were included in the analysis. Hyaluronic acid (HA) demonstrated the most favorable safety profile among the materials evaluated, with complication rates consistently below 5% and full reversibility via hyaluronidase. Polymethylmethacrylate (PMMA) was associated with surface irregularities in up to 52% of patients and offers no pharmacological reversal option. Autologous fat demonstrated highly variable reabsorption rates (30–80%) and carries a risk of systemic fat embolism. Unregulated substances — including paraffin, liquid silicone, and mineral oil — were associated with irreversible complications requiring surgical intervention in the vast majority of cases. Hyaluronic acid remains the injectable agent with the best-documented safety profile for penile augmentation. Permanent fillers and unregulated substances carry unacceptable risk profiles. The available evidence base is predominantly of low methodological quality, and well-designed, long-term randomized controlled trials are urgently needed.